Ansoff’s Growth Strategies and Financial Performance in Kenya’s Leather Industry - Waititu, Jecinta; Wambui, Maria; Kamande, Mercyline (The Journal of Accounting and Management, 2025)
Objectives: This study investigates the influence of Ansoff’s growth strategies on the financial performance of Kenya’s leather industry, which faces declining export value despite rich raw materials. It aims to offer insights to enhance competitiveness. Prior Work: Grounded in Ansoff’s Matrix, Market-Based View, and Resource-Based View theories, the study addresses gaps in empirical research linking strategic choices to financial outcomes in Africa’s leather sector. Approach: A positivist, descriptive design was used. Data were collected from 75 senior managers across 15 tannery firms using structured questionnaires, supplemented with secondary financial data. Results: Regression analysis showed that Market Penetration, Market Development, and Product Development strategies significantly influenced financial performance, explaining 46.5% of the variance. Market Penetration had the strongest impact. Implications: Firms should focus on market penetration and development for short-term gains while investing in product development for long-term innovation. Policymakers should support technology adoption and diversification. The study provides empirical evidence for academia and actionable insights for industry stakeholders. Value: This research strengthens strategic management literature in resource-rich African economies and supports evidence-based decision-making in Kenya’s leather industry.